Modelling and control of fuzzy-based systems using intelligent water drop algorithm - Dass, Anuli; Srivastava, Smriti; Gupta, Monika; Khari, Manju; Parra Fuente, Javier; Verdú, Elena (Expert Systems, 2023)
Identification and controlling of non-linear and complex dynamical systems have been a major concern and a serious topic of study in the field of adaptive control systems. Various techniques based on artificial intelligence have been used for this purpose. For modelling and control of plants, it is essential to optimize the values of the parameters associated with the respective technique. Searching the right or optimum value of the associated parameters is known as optimization. The intelligent water drop (IWD) algorithm is an optimization algorithm derived from the natural intelligence of water drop, which always chooses the shortest possible path while travelling from rivers and lakes towards oceans and seas. This paper introduces a new way of visualizing and understanding the IWD algorithm and presents its respective application in the field of modelling and controlling of non-linear dynamic systems with the help of illustrative examples. Fuzzy type-1 and recurrent fuzzy systems have been optimized using this algorithm. Its learning ability is compared with that of the grasshopper algorithm, a particle swarm optimization (PSO) based algorithm and the gradient descent method. The examples show the superiority of the IWD algorithm over the other optimization techniques.
Keywords: gradient descent; intelligent water drop algorithm; non-linear system identification and control; particle swarm optimization; recurrent fuzzy; Scopus; JCR